A search for new urban narratives in the era of globalization: The case of urban sociology in Japan. (March 2021) - Machimura, Takashi
This article aims to describe the recent changes in urban sociology in Japan, especially by focusing on dominant urban narratives and their historical background. Japanese cities have rushed through a compressed modernity since the early 20th century. The sweeping crisis in the 21st century can be regarded partially as one of its consequences. New urban crises such as disparity and poverty, loss of habitat, internal populism, and various risks are emerging. At the same time, various challenges unique to cities are also rising. Incremental and contingent restructuring has been urged through a process of both merging and colliding of 'the persistent' and 'the newly generated' factors inside of cities. How do we imagine a sustainable form of cities through repositioning them in an uncertain future? More incisive urban research is now demanded to explain the relation between the social, political, cultural, and material factors in a city.